In vitro evidence of antioxidant and anti-inflammatory effects of a new nutraceutical formulation explains benefits in a clinical setting of COPD patients - Lazzara, Valentina; Pinto, Paola; Di Vincenzo, Serena; Ferraro, Maria; Catalano, Filippo; Provinzano, Pietro; Pace, Elisabetta; Bonsignore, Maria Rosaria (Frontiers in Pharmacology, 2024)
Increased oxidative stress within the airways is associated to epithelial damage and amplification of inflammatory responses that in turn contribute to Chronic Obstructive Pulmonary Disease (COPD) progression. This study was aimed to identify whether a new formulation of N-acetylcisteine (NAC), carnitine, curcumin and B2 vitamin could counteract oxidative stress and downstream proinflammatory events promoted by cigarette smoke extract (CSE) exposure in primary bronchial epithelial cells (PBEC), both submerged/undifferentiated (S-PBEC) and cultured at the air-liquid interface (ALI-PBEC). PBEC were exposed to CSE with/without the new formulation or NAC alone and ROS production, IL-8 and IL-6 gene expression and protein release were evaluated. CSE increased ROS, IL-8 and IL-6 gene expression and protein release and the new formulation counteracted these effects. NAC alone was not effective on IL-8 and IL-6 release. The effects of a similar nutraceutical formulation were evaluated in COPD patients treated for six months. The results showed that the treatment reduced the concentration of IL-8 in nasal wash and improved quality of life. In conclusion, the tested formulation, exerting antioxidant and anti-inflammatory effects, can preserve airway epithelial homeostasis and improve clinical symptoms in COPD.